Strategi Public Relations Partai Keadilan Sejahtera (PKS) untuk Meningkatkan Partisipasi Politik Perempuan: Studi Kasus Partai Keadilan Sejahtera (PKS) Kabupaten Semarang: Ilmu Komunikasi - Musafa, Jessira; Vanel, Zon (VISA: Journal of Vision and Ideas, 2024)
Some groups, particularly those rooted in conservative Islamic interpretations, argue that Islam does not recognize gender equality in political practice. However, the Prosperous Justice Party (PKS), as an Islamic-oriented party, holds a different view. The issue in this research is the lack of awareness and knowledge about women's roles in politics. Many women may not fully understand the importance of their involvement in politics or know how to participate effectively. To address this, PKS needs to launch an educational campaign aimed at increasing understanding of women's political rights and ways to participate. This research aims to identify and outline the Public Relations strategies employed by the Prosperous Justice Party in Semarang Regency to enhance women's participation and create an inclusive society. The research uses a qualitative method. Data collection techniques in this study include interviews, observations, and documentation. Data analysis techniques consist of data reduction, data presentation, and conclusion drawing. Data validity reflects how accurate and precise the data obtained from research subjects are compared to the data revealed by the researcher. The research findings show that the public relations strategies implemented by PKS in Semarang Regency—namely strategy of publicity, strategy of persuasion, strategy of argumentation, and strategy of image—are effective in increasing women's political participation. PKS has successfully carried out effective educational campaigns through seminars, workshops, and social media to raise awareness and knowledge among women about their political roles, positively impacting increased participation. PKS has addressed the issue of limited information reach by utilizing various communication channels, including local and digital media, and establishing partnerships with community leaders, thereby broadening the dissemination and accessibility of information regarding political opportunities for women. These strategies significantly enhanced women's political engagement in Semarang Regency.